Biological aspects of sharks landed in the Fishing Port of Kutaraja, Banda Aceh, Indonesia. Issue 1 (February 2021) - Rianjuanda, D; Melanie, K; Chaliluddin, M A; Safrinawati, S
Abstract: Shark fisheries in Aceh are not supported by the availability of research-based data and information that needed to support the preservation and development of this resource. The purposes of the study were to assess the biological aspects including shark species identify and their status in IUCN, length distribution, sex ratio, and maturity stage of male shark. This study was conducted from August to October 2017 in the Fishing Port of Kutaraja, Banda Aceh. The observation survey of fish landing sites was conducted to collect the catch species composition, total length of each individual, sex, and maturity stage of male genital of shark (clasper). The results showed there are 17 species of sharks caught by some fishing gears (n = 318). Mean total length, fork length, and standard length are 122.90 cm, 110.77 cm, and 86.50 cm, respectively. The sex ratio of dominated species ( Carcharhinus sorrah, Sphyrna lewini, and Alopias pelagicus ) showed not significantly difference between males and females, based on Chi-square test. The percentage of male shark maturity for each category (NC, NFC, FC) is 52%, 13%, and 35%, respectively. The percentage of the IUCN status (threatened rare, threatened with extinction, and almost threatened) of collected species are 12%, 29%, and 41%, respectively.